2017
DOI: 10.2340/00015555-2667
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Staphylococcus aureus Colonization in Relation to Disease Severity in Adults with Atopic Dermatitis during a Five-month Follow-up

Abstract: The aim of this study was to monitor Staphylococcus aureus colonization and disease severity in adults with atopic dermatitis (AD) during 5 months. Twenty-one patients attended 3 visits each for severity SCORing of Atopic Dermatitis (SCORAD) assessment, quantitative cultures from the skin and conventional cultures from the anterior nares, tonsils and perineum. S. aureus isolates were typed for strain identity with pulsed-field gel electrophoresis (PFGE). Seventy-one percent of patients were colonized with S. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 35 publications
3
29
0
1
Order By: Relevance
“…Furthermore, recent studies of the composition of the skin microbial community have suggested that a relative abundance of bacteria such as Staphylococcus aureus and coagulase-negative staphylococcal (CoNS) species may predict the development of AD (6,7). These observations follow several decades of reports that S. aureus often colonizes lesions on the skin of patients with AD (8) and positively correlates with disease severity (9)(10)(11). Despite the large body of work to identify genetic, environmental, and microbial risk factors that may cause AD, there is as of yet no validated, cohesive hypothesis to link these observations together into a unifying pathophysiologic mechanism.…”
Section: Introductionmentioning
confidence: 73%
“…Furthermore, recent studies of the composition of the skin microbial community have suggested that a relative abundance of bacteria such as Staphylococcus aureus and coagulase-negative staphylococcal (CoNS) species may predict the development of AD (6,7). These observations follow several decades of reports that S. aureus often colonizes lesions on the skin of patients with AD (8) and positively correlates with disease severity (9)(10)(11). Despite the large body of work to identify genetic, environmental, and microbial risk factors that may cause AD, there is as of yet no validated, cohesive hypothesis to link these observations together into a unifying pathophysiologic mechanism.…”
Section: Introductionmentioning
confidence: 73%
“…Although colonization with S. aureus is generally accepted to be associated with increased severity and flares of AD, only a few studies have examined the temporal variation of colonization and spa and CC types and related this to disease severity. Our findings that only 57% of patients initially colonized with S. aureus were colonized when re‐examined after 1·5–4 years, and that 43% were colonized at only one visit, illustrate that colonization changes over time.…”
Section: Discussionmentioning
confidence: 99%
“…Even though colonization rates are high in AD, temporal variation of S. aureus clonal complex (CC) types in patients with AD has sparsely been investigated and only over short periods of time . Staphylococcus aureus is very clonal, and most patients with AD are colonized with only one CC type .…”
mentioning
confidence: 99%
“…31,32 There is a positive correlation between disease severity and S. aureus colonization of lesional and nonlesional skin in patients with AD. 32 The toxins produced by S. aureus may aggravate AD by acting as superantigens, which can activate T cells and result in the overproduction of cytokines and systemic inflammation and shock. 33 In our previous research, we demonstrated that the S. aureus toxins SEB and SEA significantly enhance the proliferative response and the release of IL-4, IL-5, IL-13 and TNF-a as well as interferon-c in the peripheral blood of patients with AD in a Chinese Han population.…”
Section: Discussionmentioning
confidence: 99%